Mārketings IT jomā - Pankratova, Jekaterina (Latvijas Universitāte, 2024)
Pētījuma objekts ir mārketings IT nozarē. Pētījuma priekšmets ir IT uzņēmumu izmantotās mārketinga stratēģijas un metodes. Darba mērķis ir veikt visaptverošu IT nozares mārketinga analīzi un izstrādāt ieteikumus mārketinga stratēģiju uzlabošanai šajā nozarē. Pētniecība un izstrāde: 1. Mārketinga pamatjēdzienu un principu izpēte IT nozarē. 2. Analizētas mārketinga stratēģiju iezīmes IT nozares uzņēmumos. 3. Veikta veiksmīgu gadījumu salīdzinošā analīze IT mārketinga jomā. 4. Veiktas intervijas ar mārketinga speciālistiem. 5. Apkopoti secinājumi un izstrādāti ieteikumi par mārketinga stratēģiju.

The object of the research is marketing in the IT sector. The subject of the research is the marketing strategies and methods used by IT companies. The purpose of this thesis is to conduct a comprehensive analysis of marketing in IT and develop recommendations for improving marketing strategies in this industry. Research and Development: 1. Studied the fundamental concepts and principles of marketing in the IT sector. 2. Analyzed the features of marketing strategies in IT companies. 3. A comparative analysis of successful cases in the field of IT marketing has been carried out. 4. Interviews with marketing specialists were conducted. 5. Conclusions are summarized and recommendations on marketing strategy are developed.
Marketing in IT
Keywords: Ekonomika un uzņēmējdarbība; IT INDUSTRY; MARKETING STRATEGY; DIGITAL MARKETING; CUSTOMER ENGAGEMENT